Law’s Ability to Further the "Menstrual Movement" - Cotropia, Christopher A. (Columbia Journal of Gender and Law, 2021)
The current menstrual movement calls for overcoming the cultural stigma associated with menstruation, achieving “menstrual equity,” and ending “period poverty.” The stigma the movement seeks to address is that menstruation is seen as taboo, unclean, and impure. The movement’s aims are twofold: First, it wants to increase awareness of menstruation and remove discrimination against those who menstruate, thus achieving menstrual equity. Second, it intends to provide greater access to menstrual hygiene products (“MHPs”), particularly for homeless and lower income people, thus eliminating period poverty. To achieve these goals, the movement is advocating to legislatively eliminate the “tampon tax” and increase access to MHPs in prisons, homeless shelters, and schools. It also supports lawsuits challenging the constitutionality of the tampon tax. Advocates view these legal changes as instrumental in furthering the goals of equity and access to MHPs that underlie the movement. This Essay discusses whether the two major legislative changes the movement advocates—repeal of the tampon tax and providing MHPs in schools for free—will actually achieve the movement’s goals. The Essay begins by explaining how these legal changes, in theory, are meant to address menstrual equity and period poverty. It then explores the operational limits to, and expressive benefits of, these legal proposals. The Essay concludes that the expressive function of demanding these legal changes, and sometimes achieving them, plays a more significant role than the laws’ actual operation in reaching the movement’s goals.